1998
DOI: 10.1021/es980374g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of California Reformulated Gasoline on Motor Vehicle Emissions. 2. Volatile Organic Compound Speciation and Reactivity

Abstract: This paper addresses the impact of California phase 2 reformulated gasoline (RFG) on the composition and reactivity of motor vehicle exhaust and evaporative emissions. Significant changes to gasoline properties that occurred in the first half of 1996 included an increase in oxygen content; decreases in alkene, aromatic, benzene, and sulfur contents; and modified distillation properties. Vehicle emissions were measured in a San Francisco Bay Area roadway tunnel in summers 1994-1997; gasoline samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 13 publications
6
123
2
Order By: Relevance
“…Fuel headspace has been seen to account for 10 -15% of emissions in other tunnel studies, 14,22 and unreacted gasoline has been seen to contribute up to or more than half of total emitted NMHC mass. 8,14,23 The higher proportion of alkanes in the summer Kilborn tunnel tests is consistent with headspace or evaporative emissions. Compared with summer gasoline, summer Kilborn tunnel tests were depleted in aromatics, and enriched in n-alkanes, n-alkenes, branched alkenes, and cycloalkanes, shifts that indicate impacts of both headspace and partial combustion of fuel.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Fuel headspace has been seen to account for 10 -15% of emissions in other tunnel studies, 14,22 and unreacted gasoline has been seen to contribute up to or more than half of total emitted NMHC mass. 8,14,23 The higher proportion of alkanes in the summer Kilborn tunnel tests is consistent with headspace or evaporative emissions. Compared with summer gasoline, summer Kilborn tunnel tests were depleted in aromatics, and enriched in n-alkanes, n-alkenes, branched alkenes, and cycloalkanes, shifts that indicate impacts of both headspace and partial combustion of fuel.…”
Section: Resultssupporting
confidence: 65%
“…Emissions of carbonyl compounds from motor vehicles have been reported by others for tests conducted in tunnels. 3,7,8 However, in the present study, analysis of duplicate samples indicated that measurement uncertainty for these compounds was large, and, thus, our measurements were not statistically significant. To sample volatile ammonia concentrations, oxalicacid coated, prebaked quartz fiber filters were used downstream of PM filters.…”
Section: Testcontrasting
confidence: 69%
See 1 more Smart Citation
“…For example, Fig. 3 indicates that current inventories have essentially no emissions of unspeciated organics for on-road gasoline sources, which stands in contrast to the data presented here and in the literature (16,17,29,(34)(35)(36)(37).…”
contrasting
confidence: 79%
“…However, an assessment of the reactivity of the total emissions from gasoline-powered vehicles before and after CaRFG indicates that reactivity declined with the introduction of CaRFG. 15,16 Because our analyses disregarded reactivity, we should tend to understate the effectiveness of CaRFG in reducing ozone. The inventory we used included estimates of mobile source emissions that were based on MVEI7G.…”
Section: Attributing An Ozone-reducingmentioning
confidence: 99%